2013
DOI: 10.1099/ijs.0.052589-0
|View full text |Cite
|
Sign up to set email alerts
|

Ogataea kolombanensis sp. nov., Ogataea histrianica sp. nov. and Ogataea deakii sp. nov., three novel yeast species from plant sources

Abstract: Nine methanol-assimilating yeast strains isolated from olive oil sediments in Slovenia, extra virgin olive oil from Italy and rotten wood collected in Hungary were found to form three genetically separated groups, distinct from the currently recognized yeast species. Sequence analysis from genes of the small subunit (SSU) rRNA, internal transcribed spacer region/5.8S rRNA, large subunit (LSU) rRNA D1/D2 domains and translational elongation factor-1α (EF-1α) revealed that the three closely related groups repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The closest relatives were Ogataea philodendri (16 substitutions equivalent to 1.45% difference), O. polymorpha (48 substitutions equivalent to 4.36% difference), and O. angusta (52 substitutions equivalent to 4.69% difference). Members of the clade rather distant to the new species were O. kodamae , known as a species associated with insects (83 substitutions equivalent to 7.55% difference) ( Mikata and Yamada, 1995 ), O. naganishii , isolated from plant exudates and rotted logs (94 substitutions equivalent to 8.55% difference) ( Kurtzman and Robnett, 2010 ; Kurtzman et al, 2011 ), Candida pignaliae , usually associated with plants (82 substitutions equivalent to 7.56% difference) ( Péter et al, 2010 ), O. histrianica (89 substitutions equivalent to 8.08% difference), O. kolombanensis (92 substitutions equivalent to 8.40% difference), and O. deakii (108 substitutions equivalent to 9.86% difference), isolated from olive oil and rotten wood ( Cadez et al, 2013 ). The assimilation profile of the proposed species differs for several traits from the closest species of the clade ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The closest relatives were Ogataea philodendri (16 substitutions equivalent to 1.45% difference), O. polymorpha (48 substitutions equivalent to 4.36% difference), and O. angusta (52 substitutions equivalent to 4.69% difference). Members of the clade rather distant to the new species were O. kodamae , known as a species associated with insects (83 substitutions equivalent to 7.55% difference) ( Mikata and Yamada, 1995 ), O. naganishii , isolated from plant exudates and rotted logs (94 substitutions equivalent to 8.55% difference) ( Kurtzman and Robnett, 2010 ; Kurtzman et al, 2011 ), Candida pignaliae , usually associated with plants (82 substitutions equivalent to 7.56% difference) ( Péter et al, 2010 ), O. histrianica (89 substitutions equivalent to 8.08% difference), O. kolombanensis (92 substitutions equivalent to 8.40% difference), and O. deakii (108 substitutions equivalent to 9.86% difference), isolated from olive oil and rotten wood ( Cadez et al, 2013 ). The assimilation profile of the proposed species differs for several traits from the closest species of the clade ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first description of the genus Ogataea was proposed on the basis of the type species Ogataea minuta ( Yamada et al, 1994 ) that showed the assimilation of the potassium nitrate and the presence of asci containing one to four ascospores of pileiform shape. To date, more than 40 species belonging to the genus Ogataea have already been described ( Péter et al, 2007 , 2008 ; Ji and Bai, 2008 ; Limtong et al, 2008 ; Cadez et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast species of the Ogataea clade share the ability to grow with methanol as the sole carbon source (Kurtzman, 2011; Čadež et al , 2013). In this clade, only O. salicorniae does not assimilate methanol (Kurtzman, 2011).…”
mentioning
confidence: 99%
“…In this clade, only O. salicorniae does not assimilate methanol (Kurtzman, 2011). In addition to the 31 known species of Ogataea listed by Kurtzman (2011), nine species belonging to this clade were described recently (Čadež et al , 2013). Most species of Ogataea are associated with rotting wood, the external surfaces of leaves or insect frass, or as minor components of yeast communities on bodies of water and olive oil (Kurtzman 2011; Koowadjanakul et al , 2011; Limtong et al , 2013; Čadež et al , 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation